2002
DOI: 10.1093/aob/mcf212
|View full text |Cite
|
Sign up to set email alerts
|

UV-B is Required for Normal Development of Oil Glands in Ocimum basilicum L. (Sweet Basil)

Abstract: Plants of Ocimum basilicum L. grown under glass were exposed to short treatments with supplementary UV-B. The effect of UV-B on volatile essential oil content was analysed and compared with morphological effects on the peltate and capitate glandular trichomes. In the absence of UV-B, both peltate and capitate glands were incompletely developed in both mature and developing leaves, the oil sacs being wrinkled and only partially filled. UV-B was found to have two main effects on the glandular trichomes. During t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 18 publications
1
36
0
3
Order By: Relevance
“…Foi demonstrado, por ex., que no manjericão (Ocimum basilicum) e no tomilho (Thymus vulgaris), duas plantas utilizadas na medicina popular e como condimentos, o completo desenvolvimento de tricomas glandulares, onde os óleos essenciais são armazenados, é luz-dependente 123,126 .…”
Section: Radiação Ultravioletaunclassified
“…Foi demonstrado, por ex., que no manjericão (Ocimum basilicum) e no tomilho (Thymus vulgaris), duas plantas utilizadas na medicina popular e como condimentos, o completo desenvolvimento de tricomas glandulares, onde os óleos essenciais são armazenados, é luz-dependente 123,126 .…”
Section: Radiação Ultravioletaunclassified
“…The terpenoids accounted for 33.84% and were found in higher amount when compared with oil obtained during the dry season (4.32%) ( Tables 2 and 4). The synthesis of some terpenoids occurs specifically in leaf structures called glandular trichomes [28] and studies have shown that in some plants the full development of these structures is light-dependent [29,30]. A greater or lesser light intensity can explain the variation of terpenoids (Tables 2 and 4) when oils from leaves of I. laurina are compared at different collection periods.…”
Section: Yield and Chemical Composition Of The Essential Oilsmentioning
confidence: 99%
“…Though, some of the earlier studies have already reported a substantial induction of essential oil and secondary metabolites in different medicinal plants due to UV-B (Ioannidis et al 2002;Chang et al 2009). Findings of the present investigation are of importance, as it seems to be the first report evaluating the impact of sUV-B exposure on holy basil under natural field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller number of studies indicates towards the positive effects of UV-B on volatile oil production in different medicinal plants (Kumari et al 2009a, b;Nitz and Schnitzler 2004;Johnson et al 1999;Maffei and Scannerini 2000). According to Ioannidis et al (2002), UV-B might be required for filling of oil glands in sweet basil (Ocimum basilicum L.). In another study, Chang et al (2009) have also reported a positive enhancement of total volatile content in the essential oil of O. basilicum L. under supplemental dose of UV-B.…”
Section: Introductionmentioning
confidence: 99%